Konsep Turas sebagai Upaya Meredam Ketegangan Hubungan Islam dan Negara (Tela’ah atas Pemikiran Abid Al-Jabiri dan Hassan Hanafi) - Abd. Aziz (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
The relationship between Islam and the state becomes a debate among Muslim intellectuals today, it did not escape because of a tradition in the community, particularly Arab, where the growth and development of Islam. The issue of the caliphate, the Imamate, the Islamic State and sebagaianya, is a matter of tradition protracted and crystallized, when all was left alone. Finally by reading back the tradition, studying it back is a relevant thing to do, as a solution to the tension the relationship between Islam and the state.